Recent Advancements and Innovations in Post-harvest Handling, Storage, and Technology for Vegetables: A Review - , Subhash Verma; , Sapan Kumar; , Vipin Kumar; , Shatrunjay Yadav; , Paras Singh; , Anurag Saurabh; , Ashutosh Kumar; , Manjul Jain (Archives of Current Research International, 2025)
In a broad sense, Vegetables are highly perishable and experience significant qualitative and quantitative losses after harvest. Advances in post-harvest handling and storage technologies have become critical interventions for maintaining quality, extending shelf life, and reducing waste. This review explores recent developments in post-harvest management, including precision harvesting tools, innovative storage solutions, and smart packaging technologies. It also examines the challenges, such as infrastructural deficiencies, and highlights future opportunities for creating more efficient and sustainable vegetable post-harvest systems. These innovations are vital for sustaining vegetable quality, improving food security, and enhancing economic viability. Recent developments in post-harvest handling and storage technologies have been crucial in addressing this issue by curing, drying, and grading, rapid cooling and refrigeration, Processing and value addition. Those innovations play crucial roles in sustaining vegetable quality and shelf life extension, thus aiding in the process of economic viability and food security. This paper examines recent trends in post-harvest management such as precision harvesting tools (such as controlled atmosphere storage, modified atmosphere packaging), cutting-edge storage systems, and smart packaging technologies. The article identifies potential areas for further research to optimize post-harvest systems worldwide.